Analysis of BSI Bank Product Marketing Strategy Through the Utilization of Information Technology at BSI KCP Nagan Raya 2 - Rosmanidar, Rosmanidar; Junaidi, Junaidi (International Asia Of Law and Money Laundering, 2024)
This research aims to analyze the marketing strategy of Bank Syariah Indonesia (BSI) products through the utilization of information technology at BSI KCP Nagan Raya 2. This research uses a qualitative method with a descriptive approach. Data was collected through interviews with the manager, marketing staff, and customers of BSI KCP Nagan Raya 2, as well as documentation studies. The results show that BSI KCP Nagan Raya 2 has effectively utilized information technology in its marketing strategy, such as the use of social media, mobile banking, and internet banking. This strategy has a positive impact on marketing performance, indicated by an increase in the number of new customers, transaction volume, and customer satisfaction. However, there are still obstacles such as a lack of customer understanding of information technology and network disruptions. This research recommends that BSI KCP Nagan Raya 2 improve customer education about digital services and strengthen information technology infrastructure.